2006
DOI: 10.1007/s11240-006-9095-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and gender in the gametophyte of Blechnum spicant L

Abstract: The growth and gender in the gametophyte of Blechnum spicant L. were strongly affected by its origin, spore or mature homogenized gametophytes, and also by the addition of plant growth regulators to the culture medium. Spore-derived gametophytes cultured in Murashige and Skoog liquid medium were females and heart-shaped, whereas those derived from mature homogenized gametophytes were shorter and male or asexual (1:3) because of the release of antheridiogen to the culture medium. In the latter, maleness was esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…In an earlier work done in our laboratory, the effect of the exogenous plant growth regulators: indol-3-acetic acid (IAA), BAP, and the gibberellins, GA 3 and GA 4?7, on the growth and sexual organ development in the SG and HG of B. spicant was reported (Menéndez et al 2006a). The results obtained revealed that HG cultured in a medium without exogenous plant growth regulators showed an inhibitory effect on their development, as well as a stimulatory effect on the antheridia formation (presumably owing to the fact of being cultured in an antheridiogen-rich medium), which was enhanced by the addition of the cytokinin, BAP, to the culture medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an earlier work done in our laboratory, the effect of the exogenous plant growth regulators: indol-3-acetic acid (IAA), BAP, and the gibberellins, GA 3 and GA 4?7, on the growth and sexual organ development in the SG and HG of B. spicant was reported (Menéndez et al 2006a). The results obtained revealed that HG cultured in a medium without exogenous plant growth regulators showed an inhibitory effect on their development, as well as a stimulatory effect on the antheridia formation (presumably owing to the fact of being cultured in an antheridiogen-rich medium), which was enhanced by the addition of the cytokinin, BAP, to the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…The maleness observed in HG might be associated with the release of antheridiogen from the mature gametophytes into the culture medium during homogenization (Menén-dez et al 2006b). Of all the phytohormones tested (Menéndez et al 2006a), only the cytokinin BAP strengthened the antheridiogen extract activity in the HG. However, SG cultured with BAP and without antheridiogen extract remained as females.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Gametophyte morphology of several species of Blechnum has already been studied, mostly in Old World species such as B. gibbum (Lab.) Mett., B. orientale L. and B. spicant (L.) Wither (Stübner, 1882;Lampa, 1901;Döpp, 1927;Karpowicz, 1927;Stokey, 1951;Stokey & Atkinson, 1952a, 1952bKachroo, 1955;Stone, 1961;Nayar, 1962;Nayar, et al, 1966;Beisvag, 1970;Cousens, 1979Cousens, , 1981Chiou, 1989;Fernández et al, 1997;Menéndez et al, 2006aMenéndez et al, , 2006b), but it is scarcely known for the American species, with the exception of some from South America, mainly Chile and Argentina (Rodríguez-Ríos, 1973;Durán & de la Sota, 1996;Pérez-García et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Banks (1999) speculated that the large number of genes involved in antheridiogen signalling in Ceratopteris may uncouple the pheromonal function of antheridiogen from the hormonal function of endogenous GAs. Reinforcing this suggestion are the varied, even contrasting, developmental and reproductive responses by gametophytes of Blechnum spicant (L.) Roth to different exogenously applied GAs (Menéndez, Revilla & Fernández, 2006a; Menéndez et al. , 2006b).…”
Section: Introductionmentioning
confidence: 86%